2015
DOI: 10.1021/acs.biochem.5b00891
|View full text |Cite
|
Sign up to set email alerts
|

Promotion or Inhibition of Islet Amyloid Polypeptide Aggregation by Zinc Coordination Depends on Its Relative Concentration

Abstract: Zinc is reported to play a complex role in islet amyloid polypeptide (IAPP) aggregation, which is associated with β-cell death in type II diabetes (T2D). Depending on their relative concentrations in vitro, zinc could either promote or inhibit IAPP aggregation. Interestingly, genomewide association studies suggested both positive and negative correlations between T2D risks and activities of a β-cell-specific zinc transporter upon mutations, which determines zinc concentration in vivo. To decipher the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 43 publications
1
39
0
Order By: Relevance
“…Here, the observed concentration-dependence for zinc on IAPP aggregation is consistent with our previous studies. 16 The experimentally observed 2.7:1 ratio with maximum aggregation inhibition is close to the predicted 2:1 molecular ratio between IAPP and C-peptide in the aggregation-incompetent heterotrimer (Figs. 1, 2).…”
supporting
confidence: 73%
See 2 more Smart Citations
“…Here, the observed concentration-dependence for zinc on IAPP aggregation is consistent with our previous studies. 16 The experimentally observed 2.7:1 ratio with maximum aggregation inhibition is close to the predicted 2:1 molecular ratio between IAPP and C-peptide in the aggregation-incompetent heterotrimer (Figs. 1, 2).…”
supporting
confidence: 73%
“…Electrostatic repulsion between protonated histidine18 (His18) was found responsible for inhibiting IAPP aggregation at low pH. 14,16 Previous studies by our group and others 1719 offered molecular insights to the binding of insulin with IAPP for understanding the inhibition mechanism. The inhibition of IAPP aggregation by insulin has also been found to suppress the aggregation-induced membrane disruption.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…186 ). Combining DMD simulations with experimental characterizations 179 , Govindan et al developed an alternative model that was consistent with the experimentally-observed concentration-dependent effect of zinc on IAPP aggregation. At low zinc/IAPP stoichiometry, the IAPP oligomers cross-linked by zinc were aggregation-prone due to high local peptide concentrations (Fig.…”
Section: Iapp and Type 2 Diabetesmentioning
confidence: 72%
“…(c) A representative IAPP tetramer with His18 (highlighted as sticks in pink) coordinated by a Zn 2+ (blue sphere) from DMD simulations. 179 The amyloidogenic sequences from each IAPP monomer are highlighted in rainbow colors. (d) A mechanistic scheme demonstrating the dependence of IAPP aggregation on relative zinc concentration.…”
Section: Figurementioning
confidence: 99%